Sociodemographic correlates of physical activity and sport among adults in Germany: 1997–2018 - Abu-Omar, Karim; Messing, Sven; Sarshar, Mustafa; Gelius, Peter; Ferschl, Susanne; Finger, Jonas; Bauman, Adrian (German Journal of Exercise and Sport Research, 2021)
Introduction Promoting physical activity (PA) is a key strategy to prevent noncommunicable diseases worldwide. In order to monitor physical activity levels in Germany, several large-scale studies have reported on prevalence rates and correlates. However, a comprehensive analysis of correlates of PA over time is currently lacking for Germany. Methods For the analysis, 13 national cross-sectional data sets were utilized. Data analysis was restricted to respondents aged 18 and older. In a first step, data sets were kept separate in order to explore social gradients of PA and sport. In the second step, data sets were pooled, demographic factors harmonized and binary logistic regressions were conducted. Results Regarding sports participation, different data sets indicate comparable social gradients. People with a higher age, lower income, lower levels of education, or a migrant background consistently have a higher risk of not engaging in sports. Compared to sports participation, social gradients are less pronounced for engaging in vigorous PA. Higher age, lower education, and lower income are also markers for an increased risk of not engaging in vigorous PA. Discussion The study confirms that factors of age, income, education and migrant background continue to contribute to differentials in sport and vigorous PA participation in Germany. For policy-making, this implies that PA promotion should focus on systems-based actions that might reduce population-wide inequalities. Future research might focus on pooling single studies with smaller samples in order to investigate PA and sports participation in specific disadvantaged target groups.<br
Keywords: Social gradients; Vigorous physical activity; Sport participation; Pooled data analysis; Correlates over time

Validity of step detection in persons with MS: evaluation of activity trackers and a disease-specific algorithm using smartphone data - Hartung, Verena; Sarshar, Mustafa; Shammas, Layal; Rashid, Asarnusch; Roullier, Paul; Maeurer, Mathias; Eilers, Caroline; Flachenecker, Peter; Pfeifer, Klaus; Tallner, Alexander (MULTIPLE SCLEROSIS JOURNAL, 2020)
CRIS-Team WoS Importer:2020-12-18